صور المحاسن البديعية وأسرارها في الثلث الأخير من القرآن الكريم، الجناس نموذجًا (دراسة تحليلية وصفية): Description of the beauties and secrets of rhetorical term "Alliteration “used in the last one third of the Holy Quran with examples (Analytical and descriptive study) - Dr Hafiz Muhammad Altaf; Muhammad Kashif Barkati (Al Manhal Research Journal, 2024)
The research aims to investigate the verses of the Holy Quran, briefing jinaas (الجناس) and its rhetorical secrets and describe the content of educational values that can be utilized and applied in Surah – in the holy Quran through Rhetorical and analytical study. Qur'anic rhetoric, as you can see in some of the references we have proven, but most of it stood at the limit of verbal study, and at the limits of the sentence. I am not claiming that I have met the right of the subject, because it requires effort that I have not for this but it should be hoping to open the doors of research and from these rhetorical studies of the Qur'an. The research is the discovery of the jinnas (الجناس) in the Qur'anic verses in the analytical, rhetorical and descriptive approach. According to this art, the style of the Qur'an is the literary style of art that addresses passion because the verses affect the souls, the words are suggestive and the ideas in it are mixed with emotion, and the main focus is that it is all in God's hands. And this wonderful artistic style affects the souls.